Data innovation: user experience with artificial intelligence-based systems (Human Factors in Design, 2021)
The purpose of this article is to reflect on the issues surrounding innovations based on artificial intelligence, from the point of view of UX Design. We seek to contextualize the growth of content, technological advances and the enhancement of data stored and processed at high speed. We deal with the innovation process and the user experience with interfaces based on artificial intelligence, technology on the rise, but with little maturity in the field of Design. A bibliographic review was carried out to generate reflections in a theoretical article. Challenges have been identified to improve the user experience with machine-based interfaces.